Cultural Introduction Application in Lembata Regency, NTT Using Android-Based Augmented Reality - Bagus Wibowo Kusumo; Arief Hermawan (SAFE-Network, 2024)
There are a lot of ways to conserve the Indonesian cultures, like using traditional things to create clothes, traditional houses, cultures, traditional dances, etc. The newest way to introduce Indonesia cultures is by making an application that can introduce the traditional culture. This research will focus in introducing the culture of Lembata Regency in Nusa Tenggara Timur using augmented reality technology. The application will use augmented reality technology based on android to show 3D product. This idea occurs because the limitation of information that shared by the government of Lembata Regency through its website. The understanding of local culture can give new experience to citizen and pushed them to filter the foreign culture that entering Indonesia by using virtual understanding. The Indonesian culture that localized in Lembata Regency NTT started to pushing back and threatened to be replaced by the foreign culture. That will make the citizen of Lembata Regency will loses their identity. The lack of information that provide by the local government, like the unavailability of local website that can be used to introduce the local culture is become the main idea for this research. The outcome of this research is an augmented reality application that can turned picture into 3D form. This application is mainly use to attract young generation awareness of the local culture.